PENGARUH KEPEMIMPINAN TRANSFORMASIONAL TERHADAP MOTIVASI KERJA DOSEN PADA UNIVERSITAS YANG BERADA DI KOTA MADIUN - Ariyani, Vivi (Widya Warta, 2011)
This research is a case study of transformational leadership impact on work motivation of lecturers. It examined the effect of transformational leadership on work motivation of lecturers of universities in Madiun municipality. The sample of the research was 68 lecturers of Widya Mandala University of Madiun and Merdeka University of Madiun in Juni-Agustus 2009 period. The data analysis was carried out by the use of classic assumption test. The result showed that there was normality with Jarque-bera test of normality, heteroskedasticity test with white heteroskedasticity test, multicolinearity test with parsial correlation among the variables, and autocorrelation test with Durbin-Watson test. Further, the study found that transformational leadership had significant influence on work motivation of lecturers. The regression coefficient was significant (p value < 0.05).